Long-Term Treatment Effect and Predictability of Spinopelvic Alignment After Surgical Correction of Adult Spine Deformity With Patient-Specific Spine Rods. Issue 7 (1st April 2020) - Kleck, Christopher J.; Calabrese, David; Reeves, Bradley J.; Cain, Christopher M.J.; Patel, Vikas V.; Noshchenko, Andriy; Burger-Van der Walt, Evalina L.
Abstract : Study Design: Retrospective case series. Objective: To evaluate the short- and long-term treatment effect (TE) of spinopelvic parameters after surgical correction of adult spine deformity (ASD) utilizing preoperative planning and patient-specific spine rods (PSSRs), and to assess the correspondence between planned and real outcomes. Summary of Background Data: PSSR have been used in ASD correction for the last decade. However, a TE and predictability of spinopelvic alignment at long-term follow-up has not been studied. Methods: Inclusion criteria: male or female; age more than 20 years; correction of ASD with PSSR; 24-month follow-up (or revision surgery). Studied parameters: sagittal vertical axis; lumbar lordosis (LL); pelvic tilt (PT); sacral slope; pelvic incidence (PI); and PI-LL. The measurement error, TE (the differences between postoperative and preoperative values), standardized TE, and predictability of the studied parameters assessed. The variables included categorical (optimal/nonoptimal) and continuous obtained by direct measurements and weighted by individual optimal values. Statistical significance was set at P  ⩽ 0.05. Results: Thirty-four patients were included: 56% women; the mean age, 63.4 (standard deviation, 12.7); at each follow-up: 32 at 1 to 3 months, 34 at 11 to 13, and 14 at 23 to 25 with 9 followed to the revision surgery. Strong or moderate TE was shown for sagittal vertical axis, LL, and PI-LL. The TE of PT and sacral slope was less significant and lower than planned. PI was not stable in 18%. The changes of continuous variables were more prominent and statistically significant then categorical. The mean values did not show significant differences between planned and postoperative outcomes except for PT. However, the individual deviations were substantial for all parameters. Significant predictability was shown only for LL and PI. Conclusion: Use of PSSR showed strong and relatively stable TE in ASD during 2 postoperative years. However, improvement of the planning accuracy may contribute to further enhancement of the method's efficacy. Level of Evidence: 4. Abstract : Supplemental Digital Content is available in the textThe treatment effect and postoperative predictability of spinopelvic alignment were studied after surgical correction of adult spine deformity with use of patient-specific spine rods manufactured according to the individual preoperative plan. The strong treatment effect was shown during 2 postoperative years. However, the predictability of the studied parameters was limited.